Efektivitas PjBL-STEM Terhadap Keterampilan Berpikir Kritis dan Motivasi Belajar Siswa Sekolah Dasar - Wati, Pulia; Nusantara, Toto; Utama, Candra (Jayapangus Press, 2024)
The 21st century requires students who have critical thinking skills and high learning motivation. PISA survey data shows that Indonesian students' knowledge of thinking skills is still very low and has not reached the standard scores set by PISA. Based on observations and interviews in elementary schools, it was found that there is still a lack of use of learning models and approaches, and teachers do not provide alternative options for student learning access. So this research aims to examine the effectiveness of PjBL-STEM on students' critical thinking skills and learning motivation. The research design used in this research is quasi experimental design. The research subjects consisted of 56 elementary school students consisting of 2 classes, namely 28 experimental class students and 28 control class students. The experimental class received PjBL-STEM learning treatment while the control class received conventional learning treatment. Data on students' critical thinking skills was obtained from the students' critical thinking skills test instrument. Student learning motivation data was obtained from the student learning motivation questionnaire. Data analysis was carried out using the independent sample t test at the significance level (sig < 0.05). The results of the research show that there are differences in students' critical thinking skills and learning motivation in classes with PjBL-STEM learning and conventional classes. This can be seen from the increase in Posttest scores and questionnaire results obtained in the PjBL-STEM class compared to conventional classes. The independent sample t test shows that the significance probability value is 0.000, which means it is smaller than α 0.05 (sig < 0.05). Therefore, PjBL-STEM has proven to be effective for elementary school students' critical thinking skills and learning motivation.